2006
DOI: 10.1159/000088355
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Loud Snoring. A Study of Prevalence and Associations in 850 Middle-Aged French Males

Abstract: Background: Most studies on habitual snoring have focused on its prevalence. However, from the clinical point of view, the intensity of snoring is of upmost importance, as it suggests the existence of sleep apnoeas. Objectives: The aim of the study was to assess the prevalence of loud snoring using a standard questionnaire and to evaluate the anthropometric and sleep characteristic differences between loud and light snorers in a sample of middle-aged males. Methods: The subjects were middle-aged active male em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
11
0
3
Order By: Relevance
“…Again this indicates, as noted above, that SS may be problematic in and of itself, if the snoring is loud enough. This is supported by a study of 850 French males, where loudness of partner reported snoring was related to daytime sleepiness (38). Furthermore, Azarbarzin and Moussavi (39) examined 42 OSA patients and 15 non-apnoeic snorers measured with a microphone over the suprasternal notch of the trachea.…”
Section: Distinction By Soundmentioning
confidence: 79%
“…Again this indicates, as noted above, that SS may be problematic in and of itself, if the snoring is loud enough. This is supported by a study of 850 French males, where loudness of partner reported snoring was related to daytime sleepiness (38). Furthermore, Azarbarzin and Moussavi (39) examined 42 OSA patients and 15 non-apnoeic snorers measured with a microphone over the suprasternal notch of the trachea.…”
Section: Distinction By Soundmentioning
confidence: 79%
“…The prevalence of habitual (almost daily) snoring was 5% that also appears lower than the reported habitual snoring prevalence of 11-40% in Caucasians [7,13,[20][21][22] and 12-26% in Asians [9,10,[23][24][25]. However, the definition of habitual snoring has varied between studies, ranging from often [13] to more than three [20], four [10] or five [9] nights per week. Demographic characteristics of study population have also varied between these studies.…”
Section: Discussionmentioning
confidence: 82%
“…El ronquido es el síntoma nocturno más frecuente y puede ser identificado con facilidad ( 31,32 ). Estudios epidemiológicos en población general informan una prevalencia de ronquido entre 18 y 55% en hombres y entre 15 y 36% en mujeres ( [47][48][49][50] ). En el Perú, Rey de Castro y col. ( 50 ) encontraron que 27% de varones y 18% de mujeres son roncadores.…”
Section: Discussionunclassified